Occupational accidents with biological material at a university hospital in São Paulo - Galon, Tanyse (2017)
This exploratory and descriptive study aimed to identify the occurrence and characteristics of work accidents (WA) with exposure to biological material among workers at a hospital in São Paulo State. Data were collected through a document survey of WA records at the hospital and further records in the electronic protocol of the Prevention System of work accidents with Biological Material in Brazilian Hospitals (REPAT). Data were analyzed using descriptive statistics and presented in tables and figures. In 2006, 94 accidents were notified that involved workers’ exposure to body fluids at the hospital. Considering the proportions of workers exposed, surgical technicians (18.75%), nursing assistants (7.78%) and biologists (4.76%) were the most affected professionals. Hypodermic needles caused the lesions in 71.62% of the cases. The WA were more frequent during medication administration (32.97%) and blood collection (15.95%). Partial data were available about the use of Individual Protection Equipment and the workers’ vaccination situation. The results revealed important indicators of accident characteristics and the gaps in records that are extremely important to elaborate an effective prevention program to minimize accident occurrence.